2015
DOI: 10.1101/013508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread localisation of lncRNA to ribosomes: Distinguishing features and evidence for regulatory roles

Abstract: The function of long noncoding RNAs (lncRNAs) depends on their location within the cell. While most studies to date have concentrated on their nuclear roles in transcriptional regulation, evidence is mounting that lncRNA also have cytoplasmic roles. Here we comprehensively map the cytoplasmic and ribosomal lncRNA population in a human cell. Three-quarters (74%) of lncRNAs are detected in the cytoplasm, the majority of which (62%) preferentially cofractionate with polyribosomes. Ribosomal lncRNA are highly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
7
1
Order By: Relevance
“…We found that mutating all translated LINC00261 sORFs simultaneously, thereby likely reducing LINC00261's ability to bind ribosomes, did not affect LINC00261 transcript levels in HEK293T cells. This indicates that, in contrast to reports suggesting that translated sORFs can regulate RNA stability by promoting nonsense-mediated RNA decay (Carlevaro-Fita et al, 2016;Tani et al, 2013), the high translation levels and multiple sORFs of LINC00261 are unlikely to be part of a LINC00261 decay pathway. It would have been interesting to determine how concurrent mutation of all sORFs in LINC00261 affects pancreatic cell differentiation.…”
Section: Translation Of Short Non-canonical Orfs In Lncrnas: Regulatcontrasting
confidence: 85%
See 1 more Smart Citation
“…We found that mutating all translated LINC00261 sORFs simultaneously, thereby likely reducing LINC00261's ability to bind ribosomes, did not affect LINC00261 transcript levels in HEK293T cells. This indicates that, in contrast to reports suggesting that translated sORFs can regulate RNA stability by promoting nonsense-mediated RNA decay (Carlevaro-Fita et al, 2016;Tani et al, 2013), the high translation levels and multiple sORFs of LINC00261 are unlikely to be part of a LINC00261 decay pathway. It would have been interesting to determine how concurrent mutation of all sORFs in LINC00261 affects pancreatic cell differentiation.…”
Section: Translation Of Short Non-canonical Orfs In Lncrnas: Regulatcontrasting
confidence: 85%
“…To systematically discriminate LINC00261's coding and noncoding roles, we individually mutated its seven most highly translated sORFs independently in hESCs, leaving the lncRNA sequence, and hence any noncoding function coupled to RNA sequence or structure, grossly intact. Each of these hESC lines either carried a homozygous frameshift mutation near the microprotein's N-terminus (for sORFs 1-6) or a full sORF deletion (sORF7; It has been suggested that ribosome association can control lncRNA transcript levels by inducing nonsense-mediated decay (NMD) (Carlevaro-Fita et al, 2016;Tani et al, 2013). Therefore, we determined whether the presence of multiple sORFs could regulate LINC00261 stability.…”
Section: One-by-one Deletion Of Linc00261's Sorfs Does Not Impact Endmentioning
confidence: 99%
“… Polysomal fractionation: RNA-seq in subcellular fractions of human cells showed that lncRNAs are present in different cellular compartments -nucleus, free cytosolic, and ribosome-associated fractions, with most being enriched in the free cytosolic [62] and in the light polysomal fraction [63]. Ribosome profiling following polysomal fractionation (Poly-Ribo-seq), allows enrichment of transcripts that are translated by only a few ribosomes and therefore likely contain small ORFs (smORFs).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Statistically, lncRNAs are mostly enriched in the cytoplasm, especially in ribosomes. LncRNAs reaching the cytoplasm will come to the default destination ribosome and may be degraded therein (van Heesch et al, 2014;Carlevaro-Fita et al, 2016). LncRNAs participate in forming partial nucleolus networks, regulating ribosome genesis, and modulating the function and structure of the nucleolus.…”
Section: Figurementioning
confidence: 99%